Electrochromic Properties of Polymers/Copolymers via Electrochemical Polymerization Based on Star-Shaped Thiophene Derivatives with Different Central Cores. Issue 4 (1st January 2017) - Li, Weijun; Chen, Lan; Pan, Yuyu; Yan, Shuanma; Dai, Yuyu; Liu, Jin; Yu, Yue; Qu, Xingxing; Song, Qingbao; Ouyang, Mi; Zhang, Cheng
Abstract : Three star-shaped thiophene derivatives, namely TPAT, PHT and TPTT with different central cores of triphenylamine, phenyl and 2, 4, 6-triphenyl-1, 3, 5-triazine respectively, were synthesized and characterized. They were further successfully prepared into the corresponding cross-linked polymers pTPAT, pPHT and pTPTT via electrochemical polymerization. The cyclic voltammetry curves showed that pPHT and pTPTT displayed the relatively higher onset oxidative potentials than pTPAT. After being applied with the positive voltages in an electrochemical cell, pTPAT exhibited the obvious electrochromic behaviors, while such phenomenons were not observed in the case of pPHT and pTPTT. The theory calculation results together with the electrochemistry properties revealed that the electrochromism of pTPAT may mainly depend on its relatively lower oxidative potential because of the introduction of triphenylamine with low ionization energy. Through the copolymerization with 3, 4-ethylenedioxythiophene (EDOT) which is also of relatively low ionization energy, pPHT-EDOT and pTPTT-EDOT both exhibited excellent electrochromic properties. The oxidative potential or ionization energy of polymer is thought to be one of the key factors determining the electrochromism.